2017
DOI: 10.2147/ott.s138011
|View full text |Cite
|
Sign up to set email alerts
|

FOLFOX regimen plus dendritic cells–cytokine-induced killer cells immunotherapy for the treatment of colorectal cancer: a meta-analysis

Abstract: PurposeTo systematically investigate the efficacy and safety of the combination of FOLFOX (oxaliplatin, 5-fluorouracil, and leucovorin) regimen and cocultured dendritic cells and cytokine-induced killer cells (DC-CIK) immunotherapy for the treatment of colorectal cancer (CRC).MethodsPublications reporting the clinical trials’ responses or safety of FOLFOX regimen combined with DC-CIK immunotherapy in treating CRC patients were searched in PubMed, Embase, Cochrane Library, China National Knowledge Internet, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…60 Accordingly, there is already clinical evidence that by stimulating dendritic cells (and also NK cells) via in vitro cytokine treatment, the anti-CRC activity of the FOLFOX scheme can be improved. 61 The mechanism of DC activation by BGs, via PAMPs, relies on direct induction of PRR signalling (e.g. TLR 4), which are generally found on antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…60 Accordingly, there is already clinical evidence that by stimulating dendritic cells (and also NK cells) via in vitro cytokine treatment, the anti-CRC activity of the FOLFOX scheme can be improved. 61 The mechanism of DC activation by BGs, via PAMPs, relies on direct induction of PRR signalling (e.g. TLR 4), which are generally found on antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous studies demonstrated the feasibility and low toxicity of CIK cell treatment for several kinds of cancer, including hepatocellular carcinoma, breast cancer, epithelial ovarian cancer, non‐small‐cell lung cancer and nasopharyngeal carcinoma . Other studies reported the effectiveness of dendritic cell (DC)–CIK/CIK immunotherapy for colorectal cancer . However, the therapeutic efficacy of CIK cell treatment for patients with mCRC is poorly understood and needs further confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…In some situations, cell‐based immunotherapy offers a valuable and more effective alternative to conventional cytotoxic therapy . A series of studies have demonstrated the efficacy of adoptive cell immunotherapy, including tumor‐infiltrating lymphocytes, antigen‐specific T lymphocytes, cytokine‐induced killer (CIK) cells and chimeric antigen receptor (CAR) T cells . Among them, CIK cells have characteristics of rapid proliferation, strong antitumor activity, broad spectrum of antitumor activity and minimal toxicity and have been demonstrated as effective in many tumors, including CRC .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations